Endothelial, smooth muscle and fibroblast cell sheet fabrication from self-assembled thermoresponsive poly(glycidyl ether) brushes. Issue 41 (9th October 2018) - Stöbener, Daniel David; Hoppensack, Anke; Scholz, Johanna; Weinhart, Marie
Abstract : Self-assembled thermoresponsive poly(glycidyl ether) brushes on polystyrene culture dishes facilitate the fabrication of vascular human cell sheets. Abstract : In this study, we introduce a platform to fabricate human dermal fibroblast (HDF), human aortic smooth muscle cell (HAoSMC) and human umbilical vein endothelial cell (HUVEC) sheets using thermoresponsive poly(glycidyl ether) coatings. Copolymer brushes based on glycidyl methyl ether (GME) and ethyl glycidyl ether (EGE) were self-assembled onto polystyrene (PS) culture substrates via the physical adsorption of a hydrophobic, photoreactive benzophenone anchor block based on the monomer 4-[2-(2, 3-epoxypropoxy)ethoxy]benzophenone (EEBP). The directed self-assembly of well-defined, end-tethered poly(GME- ran -EGE)- block -poly(EEBP) (PGE) brushes was achieved via the selective, EEBP-driven adsorption of the asymmetric block copolymer from dilute aqueous solution below its cloud point temperature (CPT). Subsequently, the PGE brush layers were covalently immobilized onto the PS surfaces by irradiation with UV light and characterized by ellipsometry, static water contact angle (CA) measurements and atomic force microscopy (AFM). We found that, by decreasing the temperature from 37 to 20 °C, the coatings undergo a pancake-to-brush transition, which triggers cell sheet detachment. In addition, cell culture parameters were optimized to allow proper adhesion and controlled detachment of confluent HDF, HAoSMC and HUVEC sheets, which can be applied in vascular tissue engineering.